A New 18F-Labeled Myocardial PET Tracer: Myocardial Uptake After Permanent and Transient Coronary Occlusion in Rats - Takahiro Higuchi; Stephan G. Nekolla; Marc M. Huisman; Sybille Reder; Thorsten Poethko; Ming Yu; Hans-Jürgen Wester; David S. Casebier; Simon P. Robinson; René Botnar; Markus Schwaiger (2008)
Etoposide is regarded as one of the main standard cytotoxic drugs for lung cancer. However, mutations in Kelch-like ECH-associated protein 1 (Keap1), the main regulator of nuclear factor erythroid 2-related factor 2 (Nrf2), are often detected in lung cancer and lead to chemoresistance. Since the aberrant activation of Nrf2 enhances drug resistance, the suppression of the Nrf2 pathway is a promising therapeutic strategy for lung cancer. We herein used the human lung adenocarcinoma cell line A549 because it harbors a Keap1 loss-of-function mutation. A treatment with β-glucan, a major component of the fungal cell wall, reduced Nrf2 protein levels; downregulated the expression of cytochrome P450 3A5, UDP glucuronosyltransferase 1A1, and multidrug resistance protein 1; and increased etoposide sensitivity in A549 cells. Furthermore, the ephrin type-A receptor 2 (EphA2) receptor was important for the recognition and biologic activity of β-glucan in A549 cells. EphA2 signaling includes nuclear factor kappa B (NF-κB), signal transducer and activator of transcription 3 (STAT3), and p38 mitogen-activated protein kinase (MAPK). However, treatment of cells with stattic (STAT3 inhibitor) or SB203580 (p38 MAPK inhibitor) did not diminish the effects of β-glucan. In contrast, knockdown of v-rel reticuloendotheliosis viral oncogene homolog B (RelB) abolished the effects of β-glucan, suggesting the involvement of the noncanonical NF-κB pathway. The β-glucan effects were also attenuated by the knockdown of WD40 Repeat protein 23 (WDR23). The β-glucan treatment and RelB overexpression induced the expression of Cullin-4A (CUL4A), which increased WDR23 ligase activity and promoted the subsequent depletion of Nrf2. These results revealed a novel property of β-glucan as a resistance-modifying agent in addition to its widely reported immunomodulatory effects for lung cancer therapy via the EphA2-RelB-CUL4A-Nrf2 axis. SIGNIFICANCE STATEMENT Chemotherapeutic resistance remains a major obstacle in cancer therapy despite extensive efforts to elucidate the underlying molecular mechanisms and overcome multidrug resistance. The present study revealed a novel resistance-modifying property of β-glucan, thereby expanding our knowledge on the beneficial roles of β-glucan and providing an alternative strategy to prevent drug resistance by cancer. The present results provide evidence for the involvement of a novel mode of NF-κB and Nrf2 crosstalk in the drug resistance phenotype.